The Voice of Gender Equality in VoD Films: A Critical Islamic Discourse Analysis - Ummah, Athik Hidayatul; Waeno, Muhamadaree (Digital Muslim Review, 2024)
This study critically examines the depiction of women’s inequality in digital films, focusing on gender disparity rooted in patriarchal culture, which endures despite Islam’s emphasis on justice and equality. The shifting behaviour of audiences in accessing information, education, and entertainment situates digital films as a powerful medium for advancing gender equality, harnessing the influence of mass media to reshape religious and cultural values. This research analyses three significant films: Yuni, Photocopier, and Before, Now and Then, chosen for their emphasis on gender equality, wide audience appeal, and recognition through national and international awards. Employing Norman Fairclough’s critical discourse analysis, the study explores textual, discursive, and socio-cultural dimensions. The findings reveal that, textually, the films highlight women’s struggles with injustice, discrimination, and violence. The discursive dimension emphasises the need for women to assert their rights and the propagation of Islamic teachings that promote gender equality and universal compassion. From a socio-cultural perspective, the study underlines that systemic injustice will persist unless concerted efforts are made to challenge patriarchal dominance and societal authority over women through the medium of film.